Regulation of Shadow Banking - Florian Halimi (2017)
The purpose of this research is to analyze and critically evaluate the regulation of the shadow banking system. The first phase of this thesis deals with the main entities and activities involved in the shadow credit intermediation chain. The thesis then analyzes the contribution of shadow banks to the 2008 financial crisis, in order to derive the main risks stemming from these entities. Proposed regulations by the Financial Stability Board serve as the foundation for further investigation concerning the assessment of potential supervision. In conclusion, this research will provide valuable information regarding proposed regulations as well as offer alternative approaches as how to deal with shadow banks and their risks.